Analisis Manajemen Konflik Konsep Diri Pada Perempuan Pekerja Seks Komersil - Ismail, Nabila; Qotuz Zuhro’ Fitriana, Ani (Jurnal Ekonomika Dan Bisnis (JEBS), 2023)
This study aims to review the motivating factors of a female perpetrator of commercial sex work who sacrifices her identity to improve her economy and necessities of life. The affixing of society's steorotype with the formation of a woman's character which is synonymous with a gentle character and her job as this woman must be good at taking care of herself. This study used qualitative research methods. The subjects of this study consisted of several respondent people through initial observation. Data collection techniques were carried out by personal interviews. From the results of this study, it can be concluded that there are some inner conflicts in the participants that often have to be mortgaged by the reality of life's needs in order to be fulfilled. And also personal factors that support a female commercial sex worker in choosing her way of life.